Graphene Functionalization Strategies From Synthesis to Applications - Khan, Anish; Jawaid, Mohammad; Neppolian, Bernaurdshaw; Asiri, Abdullah M.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses various aspects of graphene fictionalization strategies from inorganic oxides and organic moieties including preparation, design, and characterization of functionalization material and its applications. Including illustrations and tables summarizing the latest research on manufacturing, design, characterization and applications of graphene functionalization, it describes graphene functionalization using different techniques and materials and highlights the latest technologies in the field of manufacturing and design. This book is a valuable reference resource for lecturers, students, researchers and industrialists working in the field of material science, especially polymer composites.
Functionalized graphene as unprecedented prospects for nanobiocomposite -- Surfactants functionalized reduced graphene oxide and its dissolvability -- Nitrogen functionalize graphene oxide and its properties -- Graphene functionalized melamine sponge and is applications in food and environment -- Graphene functionalizations on copper by spectroscopic techniques -- Cu diped amine functionalized graphene oxide and its scope as catalysts -- Chemical functionalization of penta graphene and thermal conductivity -- Reversible osmosis of metal ions and functionalized nanoporous graphene -- Functionalized graphene and its applications in radionuclide -- Graphene-polyethylene nanocomposites -- Tuning of electronic properties of graphene oxide with various functionalities -- Graphene Functionalization and nanopolymers -- Sonochemically functionalized graphene oxide and antioxidant property -- Atomic dynamics simulation of functionalized graphene surfacefor high proficient stacking of doxorubicin -- Evaluation strategies of surface functionalities on graphene -- Ultrasound-assisted synthesis, exfoliation and functionalization of graphene derivatives -- Functionalized graphene and its medicinal applications -- Hindered phenol functionalized graphene oxide for natural rubber and its applications -- Impact of functionalized graphene oxide on gelation and scaling law of alginate in water medium -- Graphene oxide covalent functionalization for organic field effect transistors.
Keywords: Nanotechnology; Materials; Surfaces (Physics).; Nanotechnology; Materials Engineering; Surface and Interface and Thin Film